Efektivitas Metode Drill and Practice Menggunakan Media Kartu Kata Dalam Meningkatkan Kemampuan Pengenalan Huruf Pada Anak Down Syndrome - Eka Sufartianinsih Jafar; Andi Lilis Dwi Nurabdillah; Utami Lesty Maulana; Alfiah Ramdani; Yunis Liana Galib (CV. Multi Kreasi Media, 2023)
Down syndrome children are born with a variety of developmental barriers that limit their basic ability to run optimally. The basic ability that needs to be developed is to recognize letters and objects in the surrounding environment. This study aims to describe specifically related to the effectiveness of the use of word card media and drill and practice methods in letterrecognition effortsin Down syndrome children. The subjects in this study amounted to three children who had Down syndrome. Based on the results of the study, it was found that the use of word card media with drill and practice methods is effectively used to improve the ability to recognize letters in Down syndrome children, so that Down syndrome children are easier to understand simple objects and words that can be used in interacting in everyday life. The basic ability that needs to be developed is to recognize letters and objects in the surrounding environment. This study aims to describe specifically related to the effectiveness of the use of word card media and drill and practice methods in letter recognition efforts in Down syndrome children. The subjects in this study amounted to three children who had Down syndrome. Based on the results of the study, it was found that the use of word card media with the drill and practice method is effectively used to improve the ability to recognize letters in Down syndrome children, so that Down syndrome children are easier to understand simple objects and words that can be used in interacting in everyday life.